2009
DOI: 10.1093/hmg/ddp162
|View full text |Cite
|
Sign up to set email alerts
|

Five new TTF1/NKX2.1 mutations in brain-lung-thyroid syndrome: rescue by PAX8 synergism in one case

Abstract: Thyroid transcription factor 1 (NKX2-1/TITF1) mutations cause brain-lung-thyroid syndrome, characterized by congenital hypothyroidism (CH), infant respiratory distress syndrome (IRDS) and benign hereditary chorea (BHC). The objectives of the present study were (i) detection of NKX2-1 mutations in patients with CH associated with pneumopathy and/or BHC, (ii) functional analysis of new mutations in vitro and (iii) description of the phenotypic spectrum of brain-lung-thyroid syndrome. We identified three new hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
181
3
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(209 citation statements)
references
References 53 publications
14
181
3
11
Order By: Relevance
“…The mutations were introduced by site-directed mutagenesis as described earlier [Carre et al, 2009], using the sense primer 5'-CCGCGCAGGAAGCGCTGGGTGCTCTTCTCGC-3' and the antisense primer 5'-GCGAGAAGAGCACCCAGCGCTTCCTGCGCGG-3' for the NKX2-1-p.R165W mutation, and the sense primer 5'GCGTGGCGGTGCCGGTCCTGGTGAAAGACGGCAAACCGTG-3' and the antisense primer 5'-CACGGTTTGCCGTCTTTCACCAGGACCGGCACCGCCACGC-3' for the NKX2-1-p.L263fs mutation.…”
Section: Mutagenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The mutations were introduced by site-directed mutagenesis as described earlier [Carre et al, 2009], using the sense primer 5'-CCGCGCAGGAAGCGCTGGGTGCTCTTCTCGC-3' and the antisense primer 5'-GCGAGAAGAGCACCCAGCGCTTCCTGCGCGG-3' for the NKX2-1-p.R165W mutation, and the sense primer 5'GCGTGGCGGTGCCGGTCCTGGTGAAAGACGGCAAACCGTG-3' and the antisense primer 5'-CACGGTTTGCCGTCTTTCACCAGGACCGGCACCGCCACGC-3' for the NKX2-1-p.L263fs mutation.…”
Section: Mutagenesismentioning
confidence: 99%
“…earlier [Carre et al, 2009]. Nucleotide numbering reflects cDNA numbering, with +1 corresponding to the A of the ATG translation initiation codon in the reference sequence NM_003317.3.…”
Section: Introductionmentioning
confidence: 99%
“…This is predicted to cause haploinsufficiency, either as a result of a non-functional, truncated NKX2-1 protein or 50% reduction of the protein levels due to NMD degradation of the premature termination codon containing NKX2-1 mRNA allele. [6,7] While BHC, with its characteristic choreiform movements, would not commonly be confused with ataxic CP, similar cases have been reported [11,12]. Doyle et al 12 reported siblings with an NKX2-1 mutation who had congenital hypothyroidism, global developmental delay and later ataxia, choreoathetosis and dysarthria.…”
Section: Discussionmentioning
confidence: 91%
“…[6,7] While BHC, with its characteristic choreiform movements, would not commonly be confused with ataxic CP, similar cases have been reported [11,12]. Doyle et al 12 reported siblings with an NKX2-1 mutation who had congenital hypothyroidism, global developmental delay and later ataxia, choreoathetosis and dysarthria. Their mother had been diagnosed with CP during childhood; she was described as having ataxia as an adult.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation